A Papaya Leaves as a Plant-Based Pesticide to Control Pests and Plant Diseases - Purba, Rusta Malum; Muliarta, I Nengah (Formosa Journal of Sustainable Research, 2024)
The purpose of writing this article is to explore information regarding the effectiveness of papaya leaf extract in controlling plant pests and diseases. The writing method uses library research by collecting data through searches on Web of Science, Google Scholar, ScienceDirect, and Citation Index. Based on phytochemical tests of papaya leaf extract, there are several chemical compounds in the form of flavonoids, alkaloids, tannins, saponins, and terpenoids which have potential as natural ingredients for vegetable pesticides because they can affect plant pest insects. Papaya leaf extract can kill pests such as aphids, whiteflies, and caterpillars. Papaya leaf extract can also control diseases such as anthracnose and late blight. Using papaya leaf extract can help farmers increase crop yields and reduce dependence on chemical pesticides